(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article discusses effective methodological approaches, innovative tools, and individual teacher strategies for teaching native language to students with special needs within the framework of inclusive education. It also analyzes the humanistic principles of education, the use of technological advances, and issues of cooperation between the teacher, family, and society.